Pengaruh Infrastruktur Publik Terhadap Pertumbuhan Ekonomi di Kota Langsa - Iskandar; Nuraini (Fakultas Ekonomi Universitas Samudra, 2019)
The purpose of this research is to analyze the influence of road and water infrastructure partially and simultaneously on economic growth in the city of Langsa. Variables of Gross Regional Domestic Product (GRDP) as dependent or bound variables and road and water infrastructure variables as independent variables or independent variables. These data use timeseries with time periods from 2008-2017. The method used is using multiple linear regression analysis with Eviws 10 program. The resulting regression equation is Y = 4.385333 + 0.003634X1 + 9.69E-06X2. The constant value of 4.385333 is the value of the level of economic growth. From the results of the test, it can be seen that the value of the road infrastructure variable is t count <ttable (0.597539 <1.8945) and the t value is significant 0.5720> 0.05 so Ho is rejected and Ha is accepted. Thus it can be concluded that partially the road infrastructure has an effect but not significantly on the economic growth of Langsa City. Based on the results of tcount <t table (1.160841 <1.8945) and significant t value that is equal to 0.2898> 0.05 then Ho is accepted and Ha is rejected, thus it can be concluded that the Water Infrastructure partially influences but not significant to Growth Economy in Langsa City. From the results of the Ftable test ata significant level of α = 5% it is 5.5914. Therefore, the calculation of Fcount <Ftable (0.835939 <5.5914), and the significance value of 0.478353> 0.05, Ho is rejected. Then it can be stated that road infrastructure and water infrastructure simultaneously have an effect but not significantly on economic growth in Langsa City. Thus the hypothesis can be accepted. the value of R Square (R²) is 0.217923 so the determinant coefficient value is 21.7923% which means that the road infrastructure variable and the rest 78.2077% are influenced by other variables not examined in this study. Water infrastructure influences economic growth in Langsa City amounting to 21.7923%